Cognitive disorders and life quality of parkinsonism patients - I. A. Zhoukova; N. G. Zhoukova; V. M. Alifirova; F. F. Gashilova (Бюллетень сибирской медицины)
Quality of life is a new characteristic of health of patient, and efficacy of treatment. Quality of life had wide dissemination during last time. The aim of study was to exanimate and to compare quality of life patients with Parkinson’s disease which depended on gender, age, form of disease and cognitive impairment. We examined quality of life of 90 patients with Parkinson’s disease by questioner SF-36 and PDQ-39. Quality of life increased in patients with Parkinson’s disease, and depends from form and cognitive impairment.